Innovative Competence of a Teacher: Best European Practices - Olena Budnyk (Vasyl Stefanyk Precarpathian National University, 2019)
The essence of the innovative competence of the teacher in the way of integration into the world space of education. The main tendencies of teacher's training for professional innovation activity are described. Best European practices according to the using of innovative studying technologies in the work with students are examined. The author proves the need for partner collaboration, group forms of activities to solve problematic learning problems at school through Problem Based Learning. Especially, the issues of development of creative initiative of children in collective work are highlighted. The content and typical difficulties in the practical using of Blended Learning are described. It is noted that Blended Learning combines traditional and distant models of studying, it can take place not only in the lecture room but outside, in synchronous or asynchronous regimes, and it predicts an extensive using of ICT in work with students. The technology of Inquiry Based Learning in teaching STEAM school subjects is presented, especially in the process of working with remote educational laboratories and Inquiry Learning Space (ILS). Some innovative tools for their practical using according to the work with students are implemented. The importance of using Project Based Learning for integration of educational subjects in the New Ukrainian School is also characterized, which gives an opportunity to form a coherent picture of the world in them.